PERILAKU POLITIK GENERASI MILENIAL: SEBUAH STUDI PERILAKU MEMILIH (VOTING BEHAVIOR): POLITICAL BEHAVIOR OF THE MILLENNIAL GENERATION: A VOTING BEHAVIOR STUDY - Muhammad Zulfa Alfaruqy (Jurnal Psikologi Jambi, 2019)
Introduction The millennial generation had been using their suffrage during the president and vice president election. But, it is still leaving a big question about how is the voting behavior of the millennial generation. It will be important to be understood as the right strategy to obtain their vote in the next election at various competition level. This study aims to explore the factors which influence the voting behavior and categorize the type of voter from the millennial generation.Method This qualitative study using focus group discussion and questionnaire which contains open-ended questions to collect the data. It involves 38 college students of Diponegoro University which enroll the political psychology class/subject.Result The result of this study shows that voting behavior of millennial generation depends on the candidate personality, the enticement, and the voter perception, also the social environment of a candidate and the social environment of the voter. They tend to be categorized as the psychological and rational voter.Conclusion And Recommendation This study has a theoretical implication that the personality of the candidate is quite important toward the voting behavior of the millennial generation. So to get their acceptance, the candidate and victory board have to show the positivity of the candidate in addition to offer the attractive vision, mission, and future program. Keyword: millennial, rational, voting behavior. ABSTRAK Pendahuluan Generasi milenial telah menggunakan hak pilih dalam kontestasi pemilu presiden dan wakil presiden. Meskipun demikian, ada pertanyaan besar perihal bagaimana sesungguhnya perilaku memilih (voting behavior) generasi milenial guna memahami strategi yang tepat dalam memperoleh dukungan suara pada pemilu-pemilu selanjutnya, di berbagai level kompetisi. Oleh karena itu, tujuan penelitian adalah untuk mengeksplorasi faktor-faktor yang mempengaruhi perilaku memilih dan kategorisasi tipe pemilih generasi milenial. Metode Penelitian kualitatif ini menggunakan penggalian data dengan kuesioner yang berisi pertanyaan terbuka. Penelitian melibatkan 38 mahasiswa Universitas Diponegoro yang mengambil mata kuliah Psikologi Politik sebagai subjek. Hasil penelitian menunjukkan bahwa perilaku memilih dipengaruhi oleh personal kandidat, tawaran kandidat, persepsi pemilih, lingkungan sosial pemilih, dan lingkungan sosial kandidat. Mereka cenderung terkategorisasi sebagai pemilih psikologis dan rasional. Kesimpulan dan Saran Penelitian memiliki implikasi teoretis yang mendukung personal kandidat sebagai faktor yang berpengaruh dominan terhadap perilaku memilih generasi milenial. Jika ingin mendapatkan suara generasi milenial, maka kandidat dan tim sukses perlu mengedepankan figur positif kandidat, di samping mengemas tawaran visi-misi dan program kerja dalam kampanye yang menarik. Kata kunci: milenial, rasional, perilaku memilih